Constraints, Challenges, and Opportunities For Digital Business in Rural and Township Economy - Akinrinde, Olawale; Marwa, Nyankomo; Mahlaule, Misaveni (School of Business, IPB University (SB-IPB), 2024)
Background: The digital economy is expanding at an unprecedented pace worldwide, transforming industries and creating new business models. However, the adoption of digital technologies and digital business models in rural and township areas in developing countries faces numerous constraints given their contextual nuances.Purpose: This study examined the constraints, challenges and opportunities for digital business in the rural, and township economy in South Africa.Design/methodology/approach: The study employed a mixed-methods approach incorporating questionnaires and focused group discussions. The study area was two villages in Limpopo and two townships in Gauteng.Findings/Result: The study findings indicate that challenges and constraints that hinder the successful adoption and implementation of digital business in South Africa were: limited access to internet connectivity, inadequate digital infrastructure, limited digital literacy and skills, insufficient financial resources for investment in digital technologies, restricted access to affordable logistics and delivery services, concerns regarding trust and security in online transactions, competition with traditional businesses, limited access to funding for entrepreneurs, and cultural and language diversity barriers.Conclusion: Considering these findings, the research presents a set of recommendations to address these constraints and maximize the opportunities offered by digital businesses in rural and township areas contributing to the broader development goals of the nation.Originality/value (State of the art): This study offers original insights into the specific constraints, challenges, and opportunities for digital business in South Africa's rural and township economies. Employing a mixed-methods approach, highlights the unique contextual factors affecting digital adoption, providing valuable recommendations to enhance digital business integration and contribute to broader national development goals, particularly in underrepresented areas. Keywords: digital business, digital literacy, e-commerce, internet connectivity, rural economy, township economy